Improving symptom-related communication skills among cancer patients in an oncology ward: a best practice implementation project. Issue 1 (29th March 2022) - Zeng, Kai; Wang, Ning; Wang, Mei; Hu, Lijuan; Deng, Guoyu; Stephenson, Matthew; Zhang, Lili
ABSTRACT: Introduction and aims: As a symptom is a subjective perception of patients, good symptom management requires the patients to actively talk to clinicians about their symptom experience and to effectively express concerns about treatment. It has been found that the patients displayed poor communication behaviors and lacked communication knowledge and skills in the oncology ward of a tertiary hospital in PR China, indicating the need for improvement. This project aimed to promote the cancer patients' symptom-related communication with clinicians in this hospital setting. Method: A baseline audit against six evidence-based audit criteria derived from best practice recommendations was conducted, utilizing the JBI Practical Application of Clinical Evidence System tool. Identification of facilitators and barriers to best practice was then carried out and strategies were implemented to overcome identified barriers. A postimplementation audit was undertaken to assess any improvement in practice. Results: The baseline audit showed that the nurses' compliance with best practice recommendations was unsatisfactory, with five out of six criteria recording 0% compliance. Strategies including nurse education, patient symptom assessment, patient education and use of communication tools were implemented. The postimplementation audit showed significantly improved compliance in the nurses' practice with all best practice recommendations, with all audit criteria achieving at least 69% compliance. Conclusion: The project achieved improved practice in patient communication promotion across all six audit criteria. However, further effort is needed to strengthen and maintain best practice. Patient symptom-related communication behavior should be measured in the future.